PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAAN, TOTAL DEBT TO EQUITY RATIO (DER), DAN LEVERAGE TERHADAP RETURN ON ASSET PADA PERUSAHAAN MANUFAKTUR - Ficki Kristian Manurung; Ira Caroline Panjaitan; Herlin Munthe; Kiki Hardiansyah Siregar (JURNAL LENTERA BISNIS, 2025)
This study aims to examine the effect of company size, sales growth, Total Debt to Equity Ratio (DER), and leverage on Return on Assets (ROA) in 26 food & beverage manufacturing companies listed on the Indonesia Stock Exchange for the period 2021–2023. With a quantitative approach and purposive sampling technique, financial statement data were analyzed using multiple linear regression using SPSS27 to test the relationship between variables. The results show that partially only company size has a negative and significant effect on ROA, while sales growth, DER, and leverage do not have a significant effect individually. However, simultaneously the four independent variables are proven to have a positive and significant effect on ROA, indicating that the combination of operating scale and capital structure together can explain variations in the company's return on assets performance. This finding emphasizes the importance of a balance between asset expansion and external funding composition in an effort to improve capital use efficiency. The implication of this study is that company management needs to periodically review and optimize the asset structure and debt proportion to strengthen financial performance and support sustainable growth